National-strategic investment in European power transmission capacity - Daniel Huppmann; Jonas Egerer (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The transformation of the European energy system requires substantial investment in transmission capacity to facilitate cross-border trade and to efficiently integrate renewable energy sources. However, network planning in the EU is still mainly a national prerogative. In contrast to other studies aiming to identify the pan-European (continental) welfare-optimal transmission expansion, we investigate the impact of national regulators deciding on network investment strategically, with the aim of maximizing consumer surplus and generator profits in their jurisdiction. This reflects the inadequacy of current mechanisms to compensate for welfare re-allocations across national boundaries arising from network upgrades. We propose a three-stage equilibrium model to describe the Nash game between zonal planners (i.e., national governments, regulators, or system operators), each taking into account the impact of network expansion on the electricity spot market and the resulting welfare effects on the constituents within her jurisdiction. Using a four-node sample network, we identify several Nash equilibria of the game between the zonal planners, and illustrate the failure to reach the first-best welfare expansion in the absence of an effective compensation mechanism.
Keywords: L51; C61; C72; 330; electricity transmission; network expansion; Generalized Nash equilibrium (GNE); mixed-integer equilibrium problem under equilibrium constraints (MI-EPEC)